Land Office Role In Public Awareness Efforts To Increase The Systematic Complete Land Registration In The Demak District - Nur Chamid; Gunarto Gunarto; Moh Priyo Manfaat (Jurnal Akta, 2019)
Implementation of the Land Registry Systematic DETAILED under the provisions of the Regulation of the Minister of State ATR / BPNRI No. 6 in 2018 include: Determining Location Activity PTSL, Formation and Establishment Committee of Adjudication PTSL, Guidance, Data Collection, Inspection Land, Announcement Data, Issuance of Certificate of Land and delivering Land Certificate. Obstacles and Solutions Land Office Demak, Regarding the Land Registry Systematic Complete is a rebuttal or objection from the other Party on the process of land registration through PTSL carried out by the Applicant, Applicant difficult in completing the requirements, and lack of understanding Society of Land Certificate, Advice in Research These are: (1) Government Land Office Demak together in order to further improve the service to the community, particularly in the field of Land; and (2) Land Board Demak district in order to increase Legal Education or socialization of the Land.Keywords: Land Office; Systematic Complete Land Registration.